Application of functional imaging, neuronavigation, and intraoperative MR imaging in the surgical treatment of brain cavernomas - Winter, Fabian; Blair, Lisa; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2020)
Objective: The aim of this study was to investigate whether preoperative functional imaging and intraoperative magnetic resonance imaging (iMRI) facilitate surgery and improve outcomes in the surgical treatment of cavernous malformations of the brain (CM). Materials and Methods: Retrospective data analysis was performed for consecutive patients diagnosed with a CM who underwent surgical treatment at a single academic institution during a 12 year period. A total of 91 patients was eligible for analysis with a mean age of 38.8 ± 15 years (range 2–72 years). Altogether, 89.0% of CM had supratentorial and 11% infratentorial location. Results: Neuronavigation and iMRI was used in 69 (75.8%) patients with 28 (30.8%) of them together with functional MRI (fMRI) all in the supratentorial location. In 4.3% (3 cases) an intraoperative second-look surgery was performed. Altogether, a complete resection was achieved in 93% of the patients. In supratentorial surgeries, surgical times were significantly shorter in the fMRI group (p = 0.036), but altogether, infratentorial CM surgery took significantly longer (p = 0.014). Moreover, in the fMRI group, reduction of seizure medication was achieved significantly more often (p = 0.026). At an FU of 6.1± 3.1 years, 96% of the patients were assessed modified Rankin Scale 0 or 1. Conclusion: Neuronavigation together with intraoperative and functional MRI had a significant impact on resection amount, surgical time, and neurological and seizure outcome of supratentorial CM. In addition, iMRI was beneficial in few-selected cases.
CRIS-Team Scopus Importer:2020-11-27
Keywords: brain cavernomas; Functional imaging; intraoperative magnetic resonance imaging; neuronavigation